Attitude toward dementia and preferences for diagnosis in Japanese health service consumers - Oba, Hikaru (BMC Health Serv Res, 2021)
BACKGROUND: Being diagnosed with dementia is a confronting experience for any individual and their caregiver. However, a diagnosis provides opportunity for future preparation for management of the condition. This study investigated attitudes toward dementia and preferences for diagnosis among a sample of health service consumers in Japan. METHODS: Participants were patients or accompanying support persons (n = 217) who visited the specialty outpatient clinic of four hospital departments. The survey was conducted using an iPad with answers sent automatically to a secure server. The survey included items about the participants’ most feared diseases and the reasons behind those fears, estimates of dementia prevalence in Japan, and preferences regarding a diagnosis of dementia and the reasons for their preference. RESULTS: The most feared disease was cancer (43.8 %), followed by dementia (18 %). Those selecting dementia most commonly reported practical, emotional and social impacts as the reasons why they most feared this condition. Almost all participants preferred to know the diagnosis of dementia as soon as possible for themselves, with significantly fewer preferring their spouse to know as soon as possible if they had dementia (95.9 % for self vs. 67.5 % for partner/spouse, p < 0.001). On average, participants estimated that 18.1 % of Japanese people are diagnosed with dementia by age 65, while they thought that 43.7 % of Japanese people are diagnosed with dementia by age 85. CONCLUSIONS: The findings highlight a need for community education about the significant impacts of dementia on the lives of individuals and their caregivers. People were more reluctant for their spouse to receive a diagnosis as soon as possible if they had dementia. Physicians should sensitively disclose diagnosis and ensure they involve both the patient and their relatives in discussions about diagnosis disclosure.